Microfluidically supported biochip design for culture of endothelial cell layers with improved perfusion conditions. (2nd March 2015) - Raasch, Martin; Rennert, Knut; Jahn, Tobias; Peters, Sven; Henkel, Thomas; Huber, Otmar; Schulz, Ingo; Becker, Holger; Lorkowski, Stefan; Funke, Harald; Mosig, Alexander
Abstract: Hemodynamic forces generated by the blood flow are of central importance for the function of endothelial cells (ECs), which form a biologically active cellular monolayer in blood vessels and serve as a selective barrier for macromolecular permeability. Mechanical stimulation of the endothelial monolayer induces morphological remodeling in its cytoskeleton. For in vitro studies on EC biology culture devices are desirable that simulate conditions of flow in blood vessels and allow flow-based adhesion/permeability assays under optimal perfusion conditions. With this aim we designed a biochip comprising a perfusable membrane that serves as cell culture platform multi-organ-tissue-flow (MOTiF biochip). This biochip allows an effective supply with nutrition medium, discharge of catabolic cell metabolites and defined application of shear stress to ECs under laminar flow conditions. To characterize EC layers cultured in the MOTiF biochip we investigated cell viability, expression of EC marker proteins and cell adhesion molecules of ECs dynamically cultured under low and high shear stress, and compared them with an endothelial culture in established two-dimensionally perfused flow chambers and under static conditions. We show that ECs cultured in the MOTiF biochip form a tight EC monolayer with increased cellular density, enhanced cell layer thickness, presumably as the result of a rapid and effective adaption to shear stress by remodeling of the cytoskeleton. Moreover, endothelial layers in the MOTiF biochip express higher amounts of EC marker proteins von-Willebrand-factor and PECAM-1. EC layers were highly responsive to stimulation with TNF α as detected at the level of ICAM-1, VCAM-1 and E-selectin expression and modulation of endothelial permeability in response to TNF α /IFN γ treatment under flow conditions. Compared to static and two-dimensionally perfused cell culture condition we consider MOTiF biochips as a valuable tool for studying EC biology in vitro under advanced culture conditions more closely resembling the in vivo situation.